Antiplatelet Activity of Clopidogrel in Coronary Artery Bypass Graft Surgery Patients - David, J. L.; Limet, R. (Thrombosis and Haemostasis, 1999)
Clopidogrel is a recently introduced platelet ADP receptor antagonist, belonging to the thienopyridine derivatives, like its analogue ticlopidine. Its potential advantage is to be safer than ticlopidine. At 75 mg/od clopidogrel significantly inhibits platelet aggregation in ambulatory patients with symptomatic atherosclerotic disease and it prevents the recurrence of ischemic events more efficiently than aspirin. Its adequate dose in more acute situations remained to be determined. Therefore, sixty two patients with coronary artery disease were randomly assigned in four groups treated, within 24 h after coronary artery bypass graft, by clopidogrel 50 mg/od, 75 mg/od or 100 mg/od or by ticlopidine 250 mg/bid which was considered as the reference. The tolerance of clopidogrel was fairly good during the whole period of the study. Bleeding time and ex-vivo platelet aggregation induced by ADP 2 μM and 5 μM were performed at day -1, +9 and +28 after surgery. Like ticlopidine, the three dose levels of clopidogrel significantly inhibited ex-vivo platelet activity and prolonged the bleeding time at day 28. However, unlike ticlopidine, the inhibitory effects of clopidogrel were not significant at day 9, especially with 75 mg/od, a dose which was found to significantly protect patients in a chronic situation. Hence, although the clinical outcome for patients included in this limited study was the same in the four groups, these results suggest that the dose regime of clopidogrel should be more extensively investigated during the early period following coronary artery bypass graft, facing an overproduction of young and hyperreactive platelets. By analogy, the dose regime should be also investigated in other situations with an acute risk of arterial thrombotic occlusion.
Keywords: Platelets; clopidogrel; CABG surgery